Alloying-element interactions with austenite/martensite interface during quenching and partitioning of a model Fe-C-Mn-Si alloy. (15th March 2019) - Gouné, M.; Aoued, S.; Danoix, F.; Geandier, G.; Poulon-Quintin, A.; Hell, J.C.; Soler, M.; Allain, S.Y.P.
Abstract: The alloying elements partitioning from martensite to austenite during quenching and partitioning was analysed by coupling in situ High Energy X-Ray Diffraction experiments and 3D atom probe tomography. A rapid and significant carbon partitioning from martensite to austenite without any partitioning of both Mn and Si was highlighted while the interface was immobile. After a relatively short time at 400 °C, a clear Mn partitioning occurs at the vicinity of the α′/γ interface. The analysis conducted indicates that manganese equilibrates its chemical potential during partitioning and raises the issue of the Constrained Carbon Equilibrium model applicability throughout the partitioning process. Graphical abstract: Unlabelled Image